Correction: Chemical and electrochemical synthesis of cobalt hydroxides: selective phase transformation and application to distinct electrocatalytic reactions. Issue 23 (1st June 2022) - Park, Joon Yong; Kim, Ha Young; Kim, Yong-Il; Jo, So Yeong; Abbas, Syed Asad; Seo, Dongho; Ma, Ahyeon; Nam, Ki Min
Abstract : Correction for 'Chemical and electrochemical synthesis of cobalt hydroxides: selective phase transformation and application to distinct electrocatalytic reactions' by Joon Yong Park et al., J. Mater. Chem. A, 2022, ; https://doi.org/10.1039/d2ta02166h .